Market potential for personal air vehicle (PAV) concept: a Malaysian case study - Romli, Fairuz Izzuddin; Rashid, Hassan; Harmin, Mohammad Yazdi (Academic Publications, 2018)
Traffic congestion has become a common problem in many countries in the world today, including Malaysia. Several different efforts have been made such as upgrading the ground transportation infrastructures and public transport facilities, but the problem still largely remains. The idea of a dual-mode Personal Air Vehicle (PAV) concept has already been around for decades and with the increase in ground traffic problems, it is envisioned to be the possible solution. A dual-mode PAV has the capabilities of both ground and air transport vehicles. It has been published in several studies that such PAV has some advantages in terms of performance against the existing modes of transport. However, as expected with new invention, despite its clear advantages, public perception of PAV is vital for its successful implementation. This study aims to explore whether PAV concept has adequate market potential to be applied for domestic travel in Malaysia. Public perception is determined from the collected data through conducted public survey done at two major transportation hubs in Kuala Lumpur city area. All in all, it can be concluded from the survey results that the PAV concept has a good market potential and several design considerations are established for its future implementation in Malaysia.